2020
DOI: 10.1159/000507625
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Adults with Insect Venom Allergy regarding Psychological Distress, Attitudes toward the Emergency Medication, and Factual Knowledge about the Disease

Abstract: Background: Hymenoptera venom allergy (HVA) has a prevalence of 3% in adults. Although patients have no ongoing symptoms, they often suffer from an impairment of their psychological well-being and quality of life. Objective: The aim of this study was to analyze sex-specific differences regarding the psychological burden caused by this allergy and handling of the emergency medication. Method: Study participants filled out a questionnaire including sociodemographic and disease-specific characteristics, the Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Moreover, males are more likely to suffer from mastocytosis, a risk factor for venom allergy [28]. Researchers highlight that woman should be monitored more closely for allergy-associated anxiety symptoms, while men need more encouragement to carry the emergency medication [29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, males are more likely to suffer from mastocytosis, a risk factor for venom allergy [28]. Researchers highlight that woman should be monitored more closely for allergy-associated anxiety symptoms, while men need more encouragement to carry the emergency medication [29].…”
Section: Discussionmentioning
confidence: 99%
“…In a German study using sociodemographic and disease‐specific characteristics as well as the HADS, also female patients with mild SRs showed higher disease‐related anxiety levels than men 73 . As higher anxiety levels in female patients were reported in many studies, not only related to anaphylaxis, it is suggested that differences between sex with regard to mood disorders might be related to hormonal differences and diversities in the immune system 73,74 …”
Section: Hymenoptera Venommentioning
confidence: 96%
“…62,71,72 In a German study using sociodemographic and disease-specific characteristics as well as the HADS, also female patients with mild SRs showed higher disease-related anxiety levels than men. 73 As higher anxiety levels in female patients were reported in many studies, not only related to anaphylaxis, it is suggested that differences between sex with regard to mood disorders might be related to hormonal differences and diversities in the immune system. 73,74 With the use of CHVAQoLS in Polish children, a higher anxiety in girls within the group of dermal reactors was shown, but higher levels of anxiety in boys than girls with grade II reactions were observed, 4 while other studies did not find any significant differences between girls and boys.…”
Section: Factorsinfluencingthequalityoflifeof Hymenoptera Venom Aller...mentioning
confidence: 99%
See 1 more Smart Citation
“…An investigation of venom allergy found women had poorer anxiety-related HRQL, especially after experiencing anaphylactic reactions, than men. 6 Similarly, poorer asthma-related HRQL was observed in women, despite having similar disease statuses and management practices as men. 7 Studies in food allergy have reported conflicting findings on whether gender has a similar influence on HRQL and have largely only captured the perspectives of children with peanut allergy.…”
Section: Introductionmentioning
confidence: 95%